Study of predictive factors for response to 177LU-PSMA in patients with metastatic castration-resistant prostate cancer - Peslier, Hugo; Seegers, Valérie; Dufour, Pierre-Alban (Frontiers in Medicine, 2025)
IntroductionMetastatic castration-resistant prostate cancer (mCRPC) is an aggressive disease with a poor prognosis and few therapeutic options. In recent years, 177Lu-PSMA, a novel radioligand therapy, has shown promising results in patients who have failed conventional therapies. However, around 30% of patients do not respond adequately to this treatment. In this retrospective cohort study, we examined clinical, biological, and 68Ga-PSMA PET/CT-derived factors associated with poor treatment response.Materials and methodsWe conducted a retrospective cohort study including 63 patients treated at ICO Angers for progressive mCRPC following Novel Hormonal Agents and taxane-based chemotherapy. The primary endpoint was early treatment discontinuation, defined as stopping therapy at or before the 4th cycle. Secondary endpoints included PSA response and overall survival.ResultsA total of 63 patients were included in the study. Factors associated with early treatment discontinuation included a BMI < 25 kg/m2, PSA doubling time < 2 months, hemoglobin levels <10 g/dL, albumin levels <35 g/L, lactate dehydrogenase (LDH) levels >250 IU/L and alkaline phosphatase (ALP) levels >125 IU/L. On 68Ga-PSMA PET/CT imaging, low SULmax, high Total Tumor Volume, and a low PSG score were also linked to early treatment discontinuation.ConclusionThis study identified several clinical, biological, and 68Ga-PSMA PET/CT-derived factors associated with early treatment discontinuation. Patients with poor overall health, aggressive or extensive disease, or low PSMA expression are at higher risk of treatment failure.